PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KUALITAS PELAYANAN PERIZINAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PALEMBANG - Yofitri Heny Wahyuli (MAP Program Pascasarjana Universitas Sjakhyakirti, 2020)
The purpose of this study was to analyze the effect of employee competencies and employee motivation simultaneously or partially on the quality of services at the Investment and Integrated One Top Service Agency of Palembang city. This study uses a quantitative research approach with census strategies. The study population was 25 civil servants. The data used is cross section data collected using a questionnaire. The data analysis technique used is multiple linear regression with F test and t test. The results showed that employee competency and employee motivation simultaneously had a positive effect on the quality of services; employee competence partially has a positive effect on the quality of services; and employee motivation simultaneously has a positive effect on the quality of services Palembang city.